Wide ultrathin nickel-plated steel strip and preparation method thereof

By forming graphene oxide, copper and nickel plating on the surface of the steel strip, combined with high-temperature annealing treatment, the problems of unstable mechanical properties and poor corrosion resistance of the nickel-plated steel strip are solved, and its wear resistance and corrosion resistance are significantly improved.

CN119265566AInactive Publication Date: 2025-01-07JIANGSU YONGJIN METAL TECHNOLOGY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411806260.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing nickel-plated steel strips have problems such as unstable mechanical properties, poor corrosion resistance and easy brittleness and fall off of the coating.

Method used

The graphene oxide layer was formed on the steel strip surface by electroplating deposition method, and then the copper plating layer was formed on it by electroless copper plating method, and electroless nickel plating was performed on the copper plating layer. Finally, nano boron carbide was added to the composite nickel plating reagent to improve the Wear resistance of the coating.

Benefits of technology

The wear resistance and corrosion resistance of the steel belt are improved, cracks are effectively prevented, and the corrosion resistance of the coating is further enhanced through interlayer recrystallization after high-temperature annealing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of nickel-plated steel strips, in particular to a wide ultrathin nickel-plated steel strip and a preparation method thereof. The method comprises the following steps: firstly, grinding and polishing the surface of a wide ultrathin steel strip, removing dirt on the surface, strongly etching and weakly etching, and then forming a graphene oxide film layer on the surface by adopting an electroplating method; a copper plating layer and a nickel plating layer are deposited on the surface of the graphene oxide film layer in sequence through a chemical plating method; wherein a composite copper plating reagent used for chemical copper plating is obtained by mixing copper sulfate, EDTA disodium, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, deionized water, sodium hydroxide and formaldehyde, and a composite nickel plating reagent used for chemical nickel plating is obtained by mixing nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, deionized water and lactic acid. The wide ultrathin nickel-plated steel strip prepared by the method has good corrosion resistance, mechanical property and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nickel-plated steel strips, in particular to a wide ultra-thin nickel-plated steel strip and a preparation method thereof. Background Art

[0002] Steel strip, also known as strip steel, is a narrow and long steel plate material. The thickness of steel strip is generally between 0.1 and 2.0 mm. It is often used to manufacture bridges and some mechanical parts and structural parts. It is a common and indispensable important material. Like conventional steel, the iron element in the steel strip reacts with oxygen in the air to form iron oxide compounds, the so-called rust. In addition to being oxidized in the air, other chemicals in the environment, such as acidic or salt gases, liquids, etc., will also accelerate the corrosion of the steel strip.

[0003] In order to increase the service life of steel strips, people have improved the corrosion resistance of the material by nickel plating the surface of the steel strips. However, in the prior art, the single nickel plating layer has problems such as unstable mechanical properties, poor corrosion resistance, and excessive internal stress after flattening, which makes the plating layer brittle and easy to fall off. Summary of the invention

[0004] The object of the present invention is to provide a wide ultra-thin nickel-plated steel strip and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a wide ultra-thin nickel-plated steel strip and a preparation method thereof, comprising the following steps: Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; strongly etch for 60 to 90 seconds at 50 to 60°C, rinse with deionized water until neutral, then weakly etch for 60 to 120 seconds, rinse with deionized water until neutral, and set aside; Step 2: Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide solution with a mass concentration of 1-3%; using the wide ultra-thin steel strip treated in step 1 as the positive electrode and the platinum electrode as the negative electrode, electroplating in the graphene oxide solution, taking it out, drying it, and curing it to obtain a steel strip with graphene oxide electroplated on the surface; Step 3: The surface of the graphene oxide electroplated steel strip is immersed in a composite copper plating reagent, copper plating is performed at 65-70° C., taken out after 60-90 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1-1.5 μm; Step 4: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 85-90°C, taken out after 120-135 minutes, rinsed with deionized water, and dried to obtain a nickel-plated steel strip with a nickel coating thickness of 3-5 μm; and a finished product is obtained through a post-processing process.

[0006] Furthermore, in step 1, the contents of the components in the degreasing agent are: 80-85 g / L sodium hydroxide, 360-400 g / L sodium carbonate, 440-450 g / L sodium phosphate, and the remainder is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 10-15%; and the weak etching solution is a sulfuric acid solution with a mass concentration of 3-5%.

[0007] Furthermore, in step 2, the deposition voltage is 4-6V, the deposition time is 300-360s, and the thickness of the graphene oxide film is 5-10nm.

[0008] Furthermore, in step 3, the preparation method of the composite copper plating reagent is: mix copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, and deionized water, add sodium hydroxide to adjust the pH value to 12.5-12.8, heat to 50-60°C, and add formaldehyde.

[0009] Furthermore, the contents of each component in the composite copper plating reagent are: 0.035~0.04mol / L copper sulfate, 0.12~0.13mol / L disodium EDTA, 120~130mg / L potassium ferrocyanide, 120~125mg / L polyethylene glycol-400, 10~15mmol / L nickel sulfate, 12~18mmol / L sodium dihydrogen phosphate, and 0.1~0.12mol / L formaldehyde.

[0010] Furthermore, in step 4, the preparation method of the composite nickel plating reagent is: mixing nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, and deionized water, adding lactic acid to adjust the pH value to 5-5.5, to obtain the composite nickel plating reagent.

[0011] Furthermore, the contents of each component in the composite nickel plating reagent are: 20~25g / L nickel sulfate, 25~30g / L sodium dihydrogen phosphate, 10~12g / L sodium acetate, 21~23g / L sodium bicarbonate, 1~1.5g / L sodium fluoride, and 3~5g / L nano boron carbide.

[0012] Furthermore, in step 4, the post-treatment processes are continuous annealing, aging treatment, and flattening treatment in sequence.

[0013] Furthermore, during the continuous annealing process, the atmosphere is a 5% hydrogen-argon mixture, the temperature is 830-850°C, and the time is 60-120s; during the aging treatment process, the atmosphere is argon, the temperature is 420-450°C, and the time is 2-3h; during the leveling treatment process, the pressure is 6-8Mpa.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: in the technical solution of the present invention, the wear resistance of the product is improved by sequentially plating a graphene oxide layer, a copper plating layer and a nickel plating layer on the surface of the steel strip. Compared with the traditional single-layer process, the multi-layer plating can effectively prevent crack propagation; interlayer recrystallization after high-temperature annealing further improves the corrosion resistance of the coating.

[0015] In the present invention, a graphene oxide coating is first deposited on the surface of the steel strip by electroplating deposition. On the one hand, the graphene oxide layer can effectively prevent the penetration of corrosive ions and play a role of physical isolation; on the other hand, the presence of the graphene oxide layer can also prevent the occurrence of substitution reaction in the iron in the steel strip during copper plating, reduce the bonding force between the copper coating and the substrate, and thus reduce coating defects. The present invention forms a copper coating on the surface of graphene oxide by chemical copper plating. Compared with nickel and steel, copper has good flexibility. The copper coating, as an intermediate layer, reduces the stress generated during the nickel plating process and has a certain inhibitory effect on the generation of cracks in the nickel coating. Moreover, since the copper coating has a lower porosity, the bonding force and corrosion resistance between the coatings can be effectively improved. Finally, the present invention performs chemical nickel plating on the surface of the copper coating to form a nickel coating. Adding nano boron carbide to the composite nickel plating reagent can improve the wear resistance of the coating, but boron carbide will interfere with the deposition of the nickel coating, resulting in defects in the coating. Therefore, the present invention adds a small amount of nickel and phosphorus elements to the composite copper plating reagent, thereby providing catalytic sites on the copper coating and accelerating the Ni involved in the reaction during the nickel plating process. 2+ and HPO2 2- The diffusion and deposition rate is reduced, reducing the adverse effects of nano-boron carbide. DETAILED DESCRIPTION

[0016] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.

[0017] Materials used in the present invention and their sources: Nano boron carbide (model ZT-BC60) comes from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; graphene oxide (model XF033) comes from Jiangsu Xianfeng Nano Materials Technology Co., Ltd.

[0018] Embodiment 1: A wide ultra-thin nickel-plated steel strip and a method for preparing the same, comprising the following steps: Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; strongly etch for 60 seconds at 50°C, rinse with deionized water until neutral, then weakly etch for 60 seconds, rinse with deionized water until neutral, and set aside; wherein the content of each component in the degreasing agent is: 85g / L sodium hydroxide, 360g / L sodium carbonate, 445g / L sodium phosphate, and the balance is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 11%; the weak etching solution is a sulfuric acid solution with a mass concentration of 4%; Step 2: Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide solution with a mass concentration of 1%; using the wide ultra-thin steel strip treated in step 1 as the positive electrode and the platinum electrode as the negative electrode, electroplating in the graphene oxide solution for 300 seconds, taking it out and drying and curing it to obtain a steel strip with surface electroplated with graphene oxide; wherein the deposition voltage is 4V and the thickness of the graphene oxide film is 5nm; Step 3: The surface of the graphene oxide electroplated steel strip is immersed in a composite copper plating reagent, copper plating is performed at 65°C, and the strip is taken out after 60 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1 μm; wherein the preparation method of the composite copper plating reagent is: copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, and deionized water are mixed, sodium hydroxide is added to adjust the pH value to 12.5, the temperature is raised to 50°C, and formaldehyde is added; the composite copper plating reagent contains: 0.04 mol / L copper sulfate, 0.12 mol / L disodium EDTA, 125 mg / L potassium ferrocyanide, 125 mg / L polyethylene glycol-400, 10 mmol / L nickel sulfate, 12 mmol / L sodium dihydrogen phosphate, and 0.1 mol / L formaldehyde; Step 4: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 85°C, taken out after 120 minutes, rinsed with deionized water, and dried to obtain a wide ultra-thin nickel-plated steel strip with a nickel plating thickness of 3μm; after continuous annealing, aging treatment, and flattening treatment, a finished product is obtained; wherein the preparation method of the composite nickel plating reagent is: nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, and deionized water are mixed, and lactic acid is added to adjust the pH value to 5.5 to obtain a composite nickel plating reagent; the composite nickel plating reagent contains: 25g / L nickel sulfate, 30g / L sodium dihydrogen phosphate, 12g / L sodium acetate, 23g / L sodium bicarbonate, 1.2g / L sodium fluoride, 3g / L Nano boron carbide; during the continuous annealing process, the atmosphere is 5% hydrogen-argon mixed gas, the temperature is 830°C, and the time is 60s; during the aging process, the atmosphere is argon, the temperature is 420°C, and the time is 2h; during the leveling process, the pressure is 6Mpa.

[0019] Embodiment 2: A wide ultra-thin nickel-plated steel strip and a method for preparing the same, comprising the following steps: Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; strongly etch for 75 seconds at 55°C, rinse with deionized water until neutral, then weakly etch for 90 seconds, rinse with deionized water until neutral, and set aside; wherein the content of each component in the degreasing agent is: 85g / L sodium hydroxide, 360g / L sodium carbonate, 445g / L sodium phosphate, and the balance is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 11%; the weak etching solution is a sulfuric acid solution with a mass concentration of 4%; Step 2: Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide solution with a mass concentration of 1%; using the wide ultra-thin steel strip treated in step 1 as the positive electrode and the platinum electrode as the negative electrode, electroplating in the graphene oxide solution for 330 seconds, taking it out and drying and curing it to obtain a steel strip with surface electroplated graphene oxide; wherein the deposition voltage is 5V and the thickness of the graphene oxide film is 8nm; Step 3: The surface of the graphene oxide electroplated steel strip is immersed in a composite copper plating reagent, copper plating is performed at 68°C, and the strip is taken out after 75 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1.2 μm; wherein the preparation method of the composite copper plating reagent is: copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, and deionized water are mixed, sodium hydroxide is added to adjust the pH value to 12.5, the temperature is raised to 55°C, and formaldehyde is added; the composite copper plating reagent contains: 0.04 mol / L copper sulfate, 0.12 mol / L disodium EDTA, 125 mg / L potassium ferrocyanide, 125 mg / L polyethylene glycol-400, 12 mmol / L nickel sulfate, 15 mmol / L sodium dihydrogen phosphate, and 0.1 mol / L formaldehyde; Step 4: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 87°C, taken out after 130 minutes, rinsed with deionized water, and dried to obtain a wide ultra-thin nickel-plated steel strip with a nickel plating thickness of 4 μm; after continuous annealing, aging treatment, and flattening treatment, a finished product is obtained; wherein the preparation method of the composite nickel plating reagent is: nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, and deionized water are mixed, and lactic acid is added to adjust the pH value to 5.5 to obtain a composite nickel plating reagent; the composite nickel plating reagent contains: 25g / L nickel sulfate, 30g / L sodium dihydrogen phosphate, 12g / L sodium acetate, 23g / L sodium bicarbonate, 1.2g / L sodium fluoride, 4g / L Nano boron carbide; during the continuous annealing process, the atmosphere is 5% hydrogen-argon mixed gas, the temperature is 840°C, and the time is 100s; during the aging treatment process, the atmosphere is argon, the temperature is 435°C, and the time is 2.5h; during the leveling process, the pressure is 7Mpa.

[0020] Embodiment 3: A wide ultra-thin nickel-plated steel strip and a method for preparing the same, comprising the following steps: Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; strongly etch for 90 seconds at 60°C, rinse with deionized water until neutral, then weakly etch for 120 seconds, rinse with deionized water until neutral, and set aside; wherein the content of each component in the degreasing agent is: 85g / L sodium hydroxide, 360g / L sodium carbonate, 445g / L sodium phosphate, and the balance is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 11%; the weak etching solution is a sulfuric acid solution with a mass concentration of 4%; Step 2: Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide solution with a mass concentration of 1%; using the wide ultra-thin steel strip treated in step 1 as the positive electrode and the platinum electrode as the negative electrode, electroplating in the graphene oxide solution for 360 seconds, taking it out, drying it, and curing it to obtain a steel strip with surface electroplated with graphene oxide; wherein the deposition voltage is 6V and the thickness of the graphene oxide film is 10nm; Step 3: The surface of the graphene oxide electroplated steel strip is immersed in a composite copper plating reagent, copper plating is performed at 70°C, and the strip is taken out after 90 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1.5 μm; wherein the preparation method of the composite copper plating reagent is: copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, and deionized water are mixed, sodium hydroxide is added to adjust the pH value to 12.5, the temperature is raised to 60°C, and formaldehyde is added; the composite copper plating reagent contains: 0.04 mol / L copper sulfate, 0.12 mol / L disodium EDTA, 125 mg / L potassium ferrocyanide, 125 mg / L polyethylene glycol-400, 15 mmol / L nickel sulfate, 18 mmol / L sodium dihydrogen phosphate, and 0.1 mol / L formaldehyde; Step 4: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 90°C, taken out after 135 minutes, rinsed with deionized water, and dried to obtain a wide ultra-thin nickel-plated steel strip with a nickel plating thickness of 5μm; after continuous annealing, aging treatment, and flattening treatment, a finished product is obtained; wherein the preparation method of the composite nickel plating reagent is: nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, and deionized water are mixed, and lactic acid is added to adjust the pH value to 5.5 to obtain a composite nickel plating reagent; the composite nickel plating reagent contains: 25g / L nickel sulfate, 30g / L sodium dihydrogen phosphate, 12g / L sodium acetate, 23g / L sodium bicarbonate, 1.2g / L sodium fluoride, 5g / L Nano boron carbide; during the continuous annealing process, the atmosphere is 5% hydrogen-argon mixed gas, the temperature is 850°C, and the time is 120s; during the aging treatment process, the atmosphere is argon, the temperature is 450°C, and the time is 3h; during the leveling process, the pressure is 8Mpa.

[0021] Comparative Example 1: No graphene oxide layer is electroplated, and other parameters are the same as those in Example 1.

[0022] Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; strongly etch for 60 seconds at 50°C, rinse with deionized water until neutral, then weakly etch for 60 seconds, rinse with deionized water until neutral, and set aside; wherein the content of each component in the degreasing agent is: 85g / L sodium hydroxide, 360g / L sodium carbonate, 445g / L sodium phosphate, and the balance is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 11%; the weak etching solution is a sulfuric acid solution with a mass concentration of 4%; Step 2: The wide ultra-thin steel strip is immersed in a composite copper plating reagent, copper-plated at 65°C, taken out after 60 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1 μm; wherein the preparation method of the composite copper plating reagent is: copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, and deionized water are mixed, sodium hydroxide is added to adjust the pH value to 12.5, the temperature is raised to 50°C, and formaldehyde is added; the composite copper plating reagent contains: 0.04 mol / L copper sulfate, 0.12 mol / L disodium EDTA, 125 mg / L potassium ferrocyanide, 125 mg / L polyethylene glycol-400, 10 mmol / L nickel sulfate, 12 mmol / L sodium dihydrogen phosphate, and 0.1 mol / L formaldehyde; Step 3: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 85°C, taken out after 120 minutes, rinsed with deionized water, and dried to obtain a wide ultra-thin nickel-plated steel strip with a nickel plating thickness of 3μm; after continuous annealing, aging treatment, and flattening treatment, a finished product is obtained; wherein the preparation method of the composite nickel plating reagent is: nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, and deionized water are mixed, and lactic acid is added to adjust the pH value to 5.5 to obtain a composite nickel plating reagent; the composite nickel plating reagent contains: 25g / L nickel sulfate, 30g / L sodium dihydrogen phosphate, 12g / L sodium acetate, 23g / L sodium bicarbonate, 1.2g / L sodium fluoride, 3g / L Nano boron carbide; during the continuous annealing process, the atmosphere is 5% hydrogen-argon mixed gas, the temperature is 830°C, and the time is 60s; during the aging process, the atmosphere is argon, the temperature is 420°C, and the time is 2h; during the leveling process, the pressure is 6Mpa.

[0023] Comparative Example 2: No nickel sulfate and sodium dihydrogen phosphate were added to the composite copper plating reagent, and the remaining parameters were the same as those in Example 2.

[0024] Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; strongly etch for 75 seconds at 55°C, rinse with deionized water until neutral, then weakly etch for 90 seconds, rinse with deionized water until neutral, and set aside; wherein the content of each component in the degreasing agent is: 85g / L sodium hydroxide, 360g / L sodium carbonate, 445g / L sodium phosphate, and the balance is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 11%; the weak etching solution is a sulfuric acid solution with a mass concentration of 4%; Step 2: Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide solution with a mass concentration of 1%; using the wide ultra-thin steel strip treated in step 1 as the positive electrode and the platinum electrode as the negative electrode, electroplating in the graphene oxide solution for 330 seconds, taking it out and drying and curing it to obtain a steel strip with surface electroplated graphene oxide; wherein the deposition voltage is 5V and the thickness of the graphene oxide film is 8nm; Step 3: The surface of the graphene oxide electroplated steel strip is immersed in a composite copper plating reagent, copper plating is performed at 68°C, and the strip is taken out after 75 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1.2 μm; wherein the preparation method of the composite copper plating reagent is: copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, and deionized water are mixed, sodium hydroxide is added to adjust the pH value to 12.5, the temperature is raised to 55°C, and formaldehyde is added; the composite copper plating reagent contains: 0.04 mol / L copper sulfate, 0.12 mol / L disodium EDTA, 125 mg / L potassium ferrocyanide, 125 mg / L polyethylene glycol-400, and 0.1 mol / L formaldehyde; Step 4: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 87°C, taken out after 130 minutes, rinsed with deionized water, and dried to obtain a wide ultra-thin nickel-plated steel strip with a nickel plating thickness of 4 μm; after continuous annealing, aging treatment, and flattening treatment, a finished product is obtained; wherein the preparation method of the composite nickel plating reagent is: nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, and deionized water are mixed, and lactic acid is added to adjust the pH value to 5.5 to obtain a composite nickel plating reagent; the composite nickel plating reagent contains: 25g / L nickel sulfate, 30g / L sodium dihydrogen phosphate, 12g / L sodium acetate, 23g / L sodium bicarbonate, 1.2g / L sodium fluoride, 4g / L Nano boron carbide; during the continuous annealing process, the atmosphere is 5% hydrogen-argon mixed gas, the temperature is 840°C, and the time is 100s; during the aging treatment process, the atmosphere is argon, the temperature is 435°C, and the time is 2.5h; during the leveling process, the pressure is 7Mpa.

[0025] Comparative Example 3: No nano-boron carbide is added to the composite nickel plating reagent, and the other parameters are the same as those in Example 3.

[0026] Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; strongly etch for 90 seconds at 60°C, rinse with deionized water until neutral, then weakly etch for 120 seconds, rinse with deionized water until neutral, and set aside; wherein the content of each component in the degreasing agent is: 85g / L sodium hydroxide, 360g / L sodium carbonate, 445g / L sodium phosphate, and the balance is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 11%; the weak etching solution is a sulfuric acid solution with a mass concentration of 4%; Step 2: Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide solution with a mass concentration of 1%; using the wide ultra-thin steel strip treated in step 1 as the positive electrode and the platinum electrode as the negative electrode, electroplating in the graphene oxide solution for 360 seconds, taking it out, drying it, and curing it to obtain a steel strip with surface electroplated with graphene oxide; wherein the deposition voltage is 6V and the thickness of the graphene oxide film is 10nm; Step 3: The surface of the graphene oxide electroplated steel strip is immersed in a composite copper plating reagent, copper plating is performed at 70°C, and the strip is taken out after 90 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1.5 μm; wherein the preparation method of the composite copper plating reagent is: copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, and deionized water are mixed, sodium hydroxide is added to adjust the pH value to 12.5, the temperature is raised to 60°C, and formaldehyde is added; the composite copper plating reagent contains: 0.04 mol / L copper sulfate, 0.12 mol / L disodium EDTA, 125 mg / L potassium ferrocyanide, 125 mg / L polyethylene glycol-400, 15 mmol / L nickel sulfate, 18 mmol / L sodium dihydrogen phosphate, and 0.1 mol / L formaldehyde; Step 4: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 90°C, taken out after 135 minutes, rinsed with deionized water, and dried to obtain a wide ultra-thin nickel-plated steel strip with a nickel plating thickness of 5μm; after continuous annealing, aging treatment, and leveling treatment, a finished product is obtained; wherein the preparation method of the composite nickel plating reagent is: nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, and sodium fluoride are mixed, and lactic acid is added to adjust the pH value to 5.5 to obtain a composite nickel plating reagent; the composite nickel plating reagent contains: 25g / L nickel sulfate, 30g / L sodium dihydrogen phosphate, 12g / L sodium acetate, 23g / L sodium bicarbonate, and 1.2g / L sodium fluoride; during the continuous annealing treatment, the atmosphere is 5% hydrogen-argon mixed gas, the temperature is 850°C, and the time is 120s; during the aging treatment, the atmosphere is argon, the temperature is 450°C, and the time is 3h; during the leveling treatment, the pressure is 8Mpa.

[0027] Experiment: The wide ultra-thin nickel-plated steel strips prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to performance tests. (1) Neutral salt spray resistance test: At 35°C and 95% relative humidity, the strips were sprayed with sodium chloride of 5±0.5% mass concentration and saline of pH=7.0~7.2 at a spray rate of 1~2 mL / h·cm 2 , spray for 8 hours and then place for 16 hours, and then rate according to GB / T6461-2002; (2) Coating bonding strength test: WS-2005 coating scratch tester is used to test the bonding strength of the coating. The indenter is a diamond with a diameter of 200μm. A preload of 0.1N is first applied, and then gradually loaded to 100N at a loading rate of 40N / min. The indenter slides linearly at a rate of 5mm / min. When the coating falls off, it means that the coating begins to fail. At this time, the corresponding load is the bonding strength; (3) Microhardness test: According to QB / T3822, a Vickers hardness tester is used to test the microhardness to characterize the wear resistance. The experimental results are shown in Table 1.

[0028]

[0029] Conclusion: The data of Examples 1 to 3 show that the wide ultra-thin nickel-plated steel strip prepared by the present invention has good performance. The data of Example 1 and Comparative Example 1 show that after electroplating the graphene oxide layer, the corrosion resistance and bonding strength of the product are improved; the data of Example 2 and Comparative Example 2 show that after adding nickel sulfate and sodium dihydrogen phosphate to the composite copper plating reagent, the bonding strength of the coating is better; the data of Example 3 and Comparative Example 3 show that after adding nano boron carbide, the wear resistance of the coating is improved.

[0030] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a wide ultra-thin nickel-plated steel strip, characterized in that: The following steps are involved: Step 1: Take a wide ultra-thin steel strip, grind and polish its surface, remove surface oil with a degreasing agent, and rinse with deionized water until neutral; treat with a strong etching solution at 50-60°C for 60-90s, rinse with deionized water until neutral, then treat with a weak etching solution for 60-120s, rinse with deionized water until neutral, and set aside; Step 2: Ultrasonic dispersion of graphene oxide in deionized water to obtain a graphene oxide solution; using the wide ultra-thin steel strip treated in step 1 as the positive electrode and the platinum electrode as the negative electrode, electroplating in the graphene oxide solution, taking it out, drying it, and curing it to obtain a steel strip with graphene oxide electroplated on the surface; Step 3: The surface of the graphene oxide electroplated steel strip is immersed in a composite copper plating reagent, copper plating is performed at 65-70° C., taken out after 60-90 minutes, rinsed with deionized water, and dried to obtain a surface copper-plated steel strip with a copper plating thickness of 1-1.5 μm; Step 4: The copper-plated steel strip is immersed in a composite nickel plating reagent, nickel-plated at 85-90°C, taken out after 120-135 minutes, rinsed with deionized water, and dried to obtain a nickel-plated steel strip with a nickel coating thickness of 3-5 μm; and a finished product is obtained through a post-processing process.

2. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 1, characterized in that: In step 1, the contents of the components in the degreasing agent are: 80-85 g / L sodium hydroxide, 360-400 g / L sodium carbonate, 440-450 g / L sodium phosphate, and the balance is deionized water; the strong etching solution is a sulfuric acid solution with a mass concentration of 10-15%; and the weak etching solution is a sulfuric acid solution with a mass concentration of 3-5%.

3. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 1, characterized in that: In step 2, the mass concentration of the graphene oxide solution is 1-3%; the deposition voltage is 4-6 V, the deposition time is 300-360 s; and the thickness of the graphene oxide film is 5-10 nm.

4. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 1, characterized in that: In step 3, the preparation method of the composite copper plating reagent is: copper sulfate, disodium EDTA, potassium ferrocyanide, polyethylene glycol, nickel sulfate, sodium dihydrogen phosphate, and deionized water are mixed, sodium hydroxide is added to adjust the pH value to 12.5-12.8, the temperature is raised to 50-60° C., and formaldehyde is added.

5. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 4, characterized in that: The contents of each component in the composite copper plating reagent are: 0.035~0.04mol / L copper sulfate, 0.12~0.13mol / L disodium EDTA, 120~130mg / L potassium ferrocyanide, 120~125mg / L polyethylene glycol-400, 10~15mmol / L nickel sulfate, 12~18mmol / L sodium dihydrogen phosphate, and 0.1~0.12mol / L formaldehyde.

6. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 1, characterized in that: In step 4, the preparation method of the composite nickel plating reagent is: nickel sulfate, sodium dihydrogen phosphate, sodium acetate, sodium bicarbonate, sodium fluoride, nano boron carbide, and deionized water are mixed, and lactic acid is added to adjust the pH value to 5-5.5 to obtain the composite nickel plating reagent.

7. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 6, characterized in that: The contents of each component in the composite nickel plating reagent are: 20~25g / L nickel sulfate, 25~30g / L sodium dihydrogen phosphate, 10~12g / L sodium acetate, 21~23g / L sodium bicarbonate, 1~1.5g / L sodium fluoride, and 3~5g / L nano boron carbide.

8. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 1, characterized in that: In step 4, the post-treatment processes are continuous annealing, aging treatment, and flattening treatment.

9. The method for preparing a wide ultra-thin nickel-plated steel strip according to claim 8, characterized in that: During the continuous annealing process, the atmosphere is a 5% hydrogen-argon mixture, the temperature is 830~850°C, and the time is 60~120s; during the aging treatment process, the atmosphere is argon, the temperature is 420~450°C, and the time is 2~3h; during the leveling treatment process, the pressure is 6~8Mpa.

10. A wide ultra-thin nickel-plated steel strip prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • metal / carbon hybrid coating for metal conductors

    BE1024791A1

  • Steel back press-fit pretreatment process method

    CN114250455A

  • Surface treatment method for reducing secondary electron yield of oxygen-free copper

    CN114686944A

  • Graphene-metal composite film and manufacturing method thereof

    CN114822919A

  • Preparation process of chemical copper plating heat dissipation conductive sponge

    CN116534851A